1983
DOI: 10.1136/bmj.286.6381.1873
|View full text |Cite
|
Sign up to set email alerts
|

Results of Parks operation for faecal incontinence after anal sphincter injury.

Abstract: Parks operation for faecal incontinence was performed on 97 patients with total loss of anorectal control due to injury. All had sustained complete division of the anal sphincters as a result of trauma, anal surgery, or obstetric tears and either were incontinent or had been given a colostomy. In all patients the divided sphincters were repaired using an overlapping technique; in 93 the repair was protected by a temporary defunctioning stoma.There was no operative mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 7 publications
(1 reference statement)
0
12
0
1
Order By: Relevance
“…If an internal anal sphincter defect is identified, a separate imbrication of the internal anal sphincter may be undertaken. Symptom improvement in the range of 70-80% has been reported (192,193), although one study reported a lower improvement rate (194). In patients with incontinence due to a weak, but intact anal sphincter, postanal repair has been tried (195).…”
Section: Specific Treatmentmentioning
confidence: 99%
“…If an internal anal sphincter defect is identified, a separate imbrication of the internal anal sphincter may be undertaken. Symptom improvement in the range of 70-80% has been reported (192,193), although one study reported a lower improvement rate (194). In patients with incontinence due to a weak, but intact anal sphincter, postanal repair has been tried (195).…”
Section: Specific Treatmentmentioning
confidence: 99%
“…In der Literatur wurden zahlreiche operative Methoden rekonstruktiver Chirurgie der Schließmuskula-tur beschrieben. Dabei kommen die meisten Arbeiten zu dem Schluss, die neurogene Vorschädigung des Muskels habe einen signifikanten Einfluss auf das postoperative Ergebnis [6]. Wenige Arbeiten beschäftigen sich jedoch mit der Frage, wie sich die neurogene Schädigung quantitativ auf das postoperative Ergebnis auswirkt.…”
Section: Diskussionunclassified
“…However, adequate muscle mass must be present for these operations to be successful [ 15]. Full continence was achieved after anal sphincter repair in 66-96% of cases with fecal incontinence [7,16] and after postnatal repair in 72% [17], Gracilis muscle transposition can be advised when sphincter muscle has been lost [6,18], There is no large series reporting on the results of this operation; there have been scattered successful reports [19], However, the operation is more time consuming and complicated than puborectoplasty, although the two procedures have the same indication of loss of the sphincteric mass.…”
Section: Discussionmentioning
confidence: 99%